Designing a model of attachment styles in the reconciliation of emotional relationships with the mediation of communication skills in married students of Hamedan University of Medical Sciences - Shayesteh Fard, Zahra; Sobhi Gharamaleki , Naser; Zargham Hajebi, Majid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: One of the successful factors in married life is proper communication skills between couples. Various researches have shown that communication problems are one of the most common problems expressed by couples. The present research was carried out in order to provide a model of attachment styles in the reconciliation of emotional relationships with the mediation of communication skills in students of Hamedan University of Medical Sciences. Methods: The current research method was correlation and structural equation modeling. The statistical population of this study included 410 married female students of Hamedan University of Medical Sciences in 2019-20, who were selected by convenience sampling. The data were collected using the Marital Compatibility Questionnaire (Spanier, 1976), Hazan and Shaver (1985) Adult Attachment Styles Questionnaire and Christensen and Salawi (1984) Communication Skills Questionnaire. Data analysis was done by path analysis using AMOS and SPSS version 20 software. Results: The results showed that secure attachment (β=0.14; P